A Logit Analysis of Farmers' Knowledge Regarding Zero Tillage in Wheat - Singh, Dalbeer; Kaur, Prabhjot; Kaur, Manmeet (Indian Journal of Extension Education, 2017)
Zero tillage (ZT) technology in wheat has demonstrated considerable agronomic and economic benefits by reducing  energy costs and improving soil and water quality. The study attempted to find the knowledge level of farmers regarding  zero till wheat and factors associated with it. The study was conducted in the south-western district named Sri Muktsar  Sahib of Punjab. Atotal of 150 farmers were selected from the district through multistage sampling. Aknowledge test was  prepared and pre-tested on 20 non-sampled farmers. Study revealed that majority (76%) of farmers had medium level of  knowledge about ZT wheat. Farmers lacked knowledge regarding some important aspects such as application of presowing herbicide and depth of seed. Membership of co-operative society, mass media exposure, extension contacts and  participation in extension activities were found to be significantly correlated (p≤.01) with knowledge level of farmers.  Logit analysis revealed significant influence of mass media (p≤.01) and extension contacts (p≤.05) on the knowledge  level.
Keywords: Zero Tillage in Wheat; Knowledge; Logit analysis